Kesan pelaksanaan pembelajaran berasaskan masalah terhadap kemahiran pemikiran kritikal, kemahiran komunikasi lisan dan pencapaian pelajar dalam mata pelajaran Pengajian Am - Kiplie, Amit (2014)
The low achievement of pre-university students in General Studies associated with students’ weaknesses in higher order thinking skills, especially in the form of essay questions. Currently, there has not been previous studies related to Problem-Based Learning (PBL) on critical thinking skills, oral communication skills and students’ achievements in this subject. Thus, this study carried out to identify the effects of the implementation of PBL on the critical thinking skills, oral communication skills and students’ achievement in General Studies. This research is conducted by comparing two groups, i.e. the experimental and control group. An experimental study with pre-posttest of random group design was conducted on 60 pre-university students majoring in the humanities at a secondary school in Sarawak. The data are analyzed using the paired ttest technique, independent samples t-test and the hierarchical multiple regression. The results showed that there is a significant difference between groups which receiving PBL treatment with the control group in critical thinking skill, oral communication skills and students’ achievement. The experimental group showed higher mean values for all three dependent variables compared to the control group. However, hierarchical multiple regression analysis showed that PBL implementation has no direct relationship with students’ achievement. Furthermore, critical thinking skills and oral communication skills do not act as relationship mediator variables between the impact of PBL and students’ achievement in General Studies. This study contributes to students-centered learning theory, namely problem-based learning on critical thinking skills, oral communication skills and students’ achievement. It also supports PBL as teacher’s teaching strategy and students’ learning towards development of critical thinking skills, oral communication skills and the improvement of students’ achievement in General Studies subject.